WORKSHOP PENGUATAN KOMPETENSI GURU DALAM PEMBELAJARAN CODING DAN KECERDASAN ARTIFISIAL UNTUK PENGEMBANGAN KETERAMPILAN ABAD KE-21 DI SD NEGERI 1 SANGSIT, BULELENG - I Putu Eka Indrawan; Ayu Aprilyana Kusuma Dewi; Ni Nyoman Parmithi; Luh Putu Risma Noviana; I Kadek Juni Arta (Sewagati, 2025)
This community service program was carried out at SD Negeri 1 Sangsit, Buleleng, with the aim of strengthening teachers’ competencies in coding and artificial intelligence (AI)-based learning to support the development of 21st-century skills. The activity was motivated by the challenges faced by teachers who had not yet implemented assessments aligned with the learning steps, such as developing test blueprints and conducting detailed item analyses. In the context of modern education, 21st-century-oriented assessment plays a crucial role as it emphasizes authentic evaluation that integrates critical thinking, collaboration, creativity, and communication skills. Through this workshop, teachers were guided to understand the concepts of coding and AI-based learning while designing assessments relevant to real-world contexts. The program was successfully implemented with 100% realization, resulting in a significant improvement in teachers’ knowledge and skills. This was evidenced by an increase of 73% between the pretest and posttest scores. Overall, the workshop has made a tangible contribution to enhancing teachers’ digital literacy and preparedness in facing the challenges of 21st-century education.